Development of fragility function for typologies of confined mansory dwelling in Metropolitan Lima and Callao cities - Flores Terreros, Erika Nora (2019)
Development of Fragility functions are a widely used tool to estimate the vulnerability through the probability of response damage occurrence of a structure at different seismic demand. These functions are very useful for researchers, engineers, insurance companies, territorial planning planners and decision-makers. The aim of this research is to develop a methodology to estimate the vulnerability of theses confined masonry dwelling through the fragility function. An experimental database of confined masonry wall of two kind of informal brick and statistical database were used. This research present typologies of a dwelling according to the type of material, number of floors, and wall density respectively which are based on a statistical database. Besides, it describes a methodology to find the fragility functions based on experimental data tests that replicate the behavior of confined masonry walls and thus find the probability of the damage caused in this type of dwellings that exist in a great majority of the city of Metropolitan Lima and Callao.